Dīwān Jawāhir al-Sulūk fī Madā’iḥ al-Mulūk wa-Tasliyat Ḥuzn al-ʿĀshiq al-Mahlūk - ʿUmānī, Hilāl b. Saʿīd b. Thānī b. Ṣāliḥ b. ʿArrāba al- (Ministry of National Heritage and Culture, 1984)
His father was Saʿīd b. Thānī b. Ṣāliḥ b. ʿArrāba. This edition is based on a copy (Muswadda) of a MS; both the original MS and its copy were written by the author himself; the copy of the original was copied 1342/1923-4
Keywords: Poésie -- Oman

al-Šiʿr al-ʿumānī: muqauwimātuhū wa-ittiǧāhātuhū wa-ḫaṣāʾiṣuhū al-fannīya - ʿAlī, ʿAlī ʿAbd-al-Ḫāliq (Maktabat ad-dirāsāt al-adabīya, 1984)
Keywords: Poésie -- Oman